CFD analysis of a diaphragm free-piston Stirling cryocooler. (October 2016) - Caughley, Alan; Sellier, Mathieu; Gschwendtner, Michael; Tucker, Alan
Highlights: Computational fluid dynamics analysis of a novel free-piston Stirling cryocooler. Transient model of closed gas volume with heat transfer. Validated with gas spring dynamics experiments of piston-in-cylinder compression. The Peclet number vs work at the 'piston face' or polytropic index used for validation. Full model of Stirling cryocooler was modelled and predicted similar results to experiment. Abstract: This paper presents a Computational Fluid Dynamics (CFD) analysis of a novel free-piston Stirling cryocooler that uses a pair of metal diaphragms to seal and suspend the displacer. The diaphragms allow the displacer to move without rubbing or moving seals. When coupled to a metal diaphragm pressure wave generator, the system produces a complete Stirling cryocooler with no rubbing parts in the working gas space. Initial modelling of this concept using the Sage modelling tool indicated the potential for a useful cryocooler. A proof-of-concept prototype was constructed and achieved cryogenic temperatures. A second prototype was designed and constructed using the experience gained from the first. The prototype produced 29 W of cooling at 77 K and reached a no-load temperature of 56 K. The diaphragm's large diameter and short stroke produces a significant radial component to the oscillating flow fields inside the cryocooler which were not modelled in the one-dimensional analysis tool Sage that was used to design the prototypes. Compared with standard pistons, the diaphragm geometry increases the gas-to-wall heat transfer due to the higher velocities and smaller hydraulic diameters. A Computational Fluid Dynamics (CFD) model of the cryocooler was constructed to understand the underlying fluid-dynamics and heat transfer mechanisms with the aim of further improving performance. The CFD modelling of the heat transfer in the radial flow fields created by the diaphragms shows the possibility of utilizing the flat geometry for heat transfer, reducing the need for, and the size of, expensive heat exchangers. This paper presents details of a CFD analysis used to model the flow and gas-to-wall heat transfer inside the second prototype cryocooler, including experimental validation of the CFD to produce a robust analysis.